Audit Sistem Informasi Aplikasi Digipop OOH Menggunakan Framework Cobit 5 - Esra Novalina Panjaitan; Eva Zuraidah (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Information system audits are carried out to identify and ensure that existing system procedures in the company function properly, using the Cobit 5 framework to audit information systems of Digipop OOH Application located at PT. Media Indra Buana because previously there had never been a comprehensive audit of the information system used by the company so that the operational services of the information system could not be ascertained in accordance or not with the standards of the company's needs. Research is collected by quantitative capability analysis. The audit results with the highest value, namely the DSS01 domain, received a Maturity Level value of 15.07 with a Fully Achievement value and a gap value of each DSS01.01 sub domain with gap value 10.42, DSS01.02 with gap value 11.33, DSS01.03 with gap value 11.11, DSS01.04 with gap value 11.00 and DSS01.05 with gap value 11.51 from the target level 4. While the DSS02 domain received a Maturity Level value of 10.84 with a Fully Achievement value and a gap value of each DSS02.01 sub domain with gap value 6.87, DSS02.02 with gap value 6.69, DSS02.03 with gap value 6.85, DSS02.04 with gap value 6.80, DSS02.05 with gap value 6.63, DSS02.06 with gap value 7.05 and DSS02.07 with gap value 6.97 from the target level 4. The results of GAP analysis obtained from DSS01 and DSS02 have reached the target level